Ultrasonic monitoring of insulated block joints. (March 2019) - Stephen, JT; Hardwick, C; Beaty, P; Lewis, R; Marshall, MB
Insulated block joints are essential components used in railway tracks. They are divided into circuits and are used for train detection and signalling. However, they also represent a weak point in the track system and have a finite life. Condition monitoring of these components for planning preventative maintenance is currently labour intensive, and can be significantly expensive for the rail operator. In this study, insulated block joints were fatigued via shear load, whilst being condition monitored for degradation using a normally incident ultrasonic technique. Tests were also initially performed on lap-joints and shear specimens to further understand the response of the ultrasonic signal to failure of the adhesive layer under controlled conditions. Dynamic reflection coefficients as well as the applied load were recorded in all tests, and results were compared to failure zones on the specimens. The results showed that the ultrasonic technique was able to determine the onset of failure and de-bonding of the adhesive layer in addition to degradation and wear. The technique was also able to highlight differences in performance between two different liners, pultruded glass reinforced polyester resin and a flexible glass fibre sheet, with the latter showing improved resistance. The outcomes of this study have highlighted the viability of condition monitoring insulated block joints using an ultrasonic approach and have provided a basis for a future field trial.